The deubiquitinase USP24 suppresses ferroptosis in triple-negative breast cancer by stabilizing DHODH protein - Li Yang; Xiaoqin An; Shangzhu Yang; Xiaowen Lin; Ziyuan Chen; Qian Xue; Xi Chen; Yuan Wang; Ding Yan; Shirui Chen; Yuqing Fan; Daolin Tang; et al. (Cell Death and Disease)
Abstract Triple-negative breast cancer (TNBC) is an aggressive subtype of invasive breast cancer characterized by limited treatment options and a poor prognosis. While ferroptosis, an iron-dependent form of regulated cell death, plays a role in tumor suppression, its specific molecular mechanisms in TNBC remain largely unexplored. In this study, we identify deubiquitinase USP24 as the most significantly altered enzyme among key deubiquitinating enzymes during ferroptosis in human TNBC cells. Silencing USP24 enhances ferroptosis-mediated tumor suppression in TNBC cells. Mechanistically, USP24 interacts directly with dihydroorotate dehydrogenase (DHODH) and deubiquitinates it, a process critical for maintaining coenzyme Q reduction and protecting cells from lipid peroxidation. Consistently, pharmacological inhibition of USP24 synergizes strongly with ferroptosis inducers in both in vitro and in vivo models via a DHODH-dependent pathway. These findings highlight USP24 as a potential therapeutic target to enhance ferroptosis sensitivity in TNBC.